Childhoods in the Face of Racism: theses for a good fight - Renato Noguera; Luciana Pires Alves (Universidade Federal do Rio Grande do Sul, 2019)
This article briefly discusses childhood as notion, category and concept. It will problematize racism and formulations that associate Africa with the humanity's childhood. The goal is to face adulthood as the greater danger of life. The text brings results from field researches accomplished in 2016 and 2017, and an analysis of the film Colors and boots (2010); in both situations, black children are faced with social-racial challenges. From dialogues with several authors, such as Mbembe, Oyewumi and Bispo dos Santos, it proposes children's theses to overcome racism for the surplus-value of life to be an affirmation of childhood as a way of putting the desire beyond the lack and pitfalls of the commodity.